Where are the ‘Asturian’ dwellings?: an integrated survey programme on the Mesolithic of northern Spain - Arias, Pablo; Cubas, Miriam; Fano, Miguel Ángel; Pardo, Jesús F. Jordá; Salzmann, Christoph; Teichner, Felix; Teira, Luis C. (Antiquity, 2015)
, - Mesolithic hunter-gatherer settlements generally leave ephemeral archaeological traces and are notoriously difficult to detect. Nowhere is this more so than on the northern coast of Spain, despite a long tradition of Mesolithic research. In this project, evidence of Mesolithic activity together with the geomorphological and topographical suitability of particular locations were used to select areas for large-scale geophysical survey. The results demonstrate the potential of the new methodology: magnetometry survey at El Alloru revealed the very first Asturian open-air settlement site to be discovered.